Analysis of Liquid Organic Fertilizer Azolla sp and Chicken Manure on the Growth and Yield of Shallot Plants - Suryani Sajar; Andi Setiawan; Adela Tri Anzani (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze Azolla sp liquid organic fertilizer and chicken manure. Tests on shallot plants were carried out to see the effect of organic fertilizer on growth and yield. The research method used a factorial Randomized Block Design (RAK) consisting of 2 factors with 16 combinations and 3 blocks. The first factor is the provision of azola liquid organic fertilizer consisting of 4 levels : 0 ml/l water/m2, 200 ml/l water/m2, 400 ml/l water/m2, 600 ml/l water/m2. The second factor is the provision of chicken manure consisting of 4 levels : 0 kg/m2, 0.5 kg/m2, 1.0 kg/m2 and 1.5 kg/m2. Azolla liquid organic fertilizer contains 0.03% total N, 0.11% P2O5, 0.59% K2O, 1.44% organic C, and 3.88% pH. The results of chicken manure analysis contain 1.73% Nitrogen (N), 1.45% Phospor (P), 1.12% Potassium (K), and 18.15% Organic C. Both types of fertilizers do not meet the minimum technical requirements for SNI organic fertilizers. The provision of azola liquid organic fertilizer has a significant effect on the parameters of the number of tillers, number of bulb/m2, wet weight of bulb/m2, and dry weight of bulb/m2. The provision of azola liquid organic fertilizer 600 ml/liter of water/m2 has the best effect on all observation parameters. The provision of chicken manure has a significant effect on the parameters of plant height, number of leaves, number of shoots, number of bulb/m2, wet weight of bulb/m2, dry weight of bulb/m2. The dose of chicken manure 1.5 kg/m2 showed the best effect for all observation parameters. The interaction of the provision of liquid organic fertilizer azolla and chicken manure was not significantly different in all treatments.